User Generated Content Strategi untuk Menarik Pembelian Produk Ramah Lingkungan oleh Gen Z - I Wayan Suardika; Ni Kadek Winda Yanti (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Abstract This study aims to analyze the influence of online brand experience and trust, community reviews and opinions, and green signaling and social status on the purchase intention of Generation Z for Sensatia Botanicals products. The study population consisted of Generation Z consumers in Bali who actively use Sensatia Botanicals, with a purposive sample of 100 respondents. Data were collected through online and offline questionnaires and analyzed using PLS-SEM to test validity, reliability, and relationships among variables. The results indicate that all three independent variables have a positive and significant effect on purchase intention. Online brand experience and trust provide consistent digital brand interactions, community reviews and opinions enhance credibility through UGC, and green signaling and social status increase symbolic value for young consumers. These findings contribute theoretically to sustainable digital marketing literature and practically guide local brands in managing UGC strategies to boost Generation Z’s purchase intention.